Functionalized carbon nanotubes for 3D-printed PLA-nanocomposites: Effects on thermal and mechanical properties. (June 2022) - Bortoli, L.S. De; Farias, R. de; Mezalira, D.Z.; Schabbach, L.M.; Fredel, M.C.
Abstract: PLA-based nanocomposites are of great interest to biomedical applications due to the biocompatibility and biodegradability of the Poly (lactic acid) (PLA), being, therefore, widely explored for application in additive manufacturing by fused filament fabrication (FFF). In this context, carbon nanotubes (CNT) have been an attractive additive to improve the mechanical strength of 3D printed PLA parts. However, a good dispersion of the CNT in the PLA matrix is essential to guarantee that it acts as a reinforcing material. Functionalized carbon nanotubes are able to increase the dispersibility and interaction of carbon nanotubes with polymers. Nonetheless, there is very limited information available about the incorporation of functionalized CNT in 3D printed PLA parts produced by FFF. In this study, CNT functionalization was performed with HNO3 solution to create defects and incorporate oxygen functional groups on the CNT surface in order to evaluate its influence on thermal and mechanical properties of 3D-printed PLA/CNT nanocomposites. The results indicated that functionalized CNTs (f-CNT) presented a better dispersion in the matrix and act as more effective nucleating agents for PLA crystallization, when compared with the use of commercial CNT (c-CNT). The addition of only 0.5 wt% of f-CNT was enough to provide a significant increase of the mechanical strength of the 3D printed parts (from 29.4 ± 0.7 MPa for PLA/c-CNT to 41.6 ± 1.4 MPa for PLA/f-CNT) and provide better interfacial adhesion between 3D printed layers, maintaining the thermal stability of the nanocomposites. Dynamic-mechanical analyses indicated a significant increase in the storage modulus (~ 43% at 37 °C) when f-CNT was used as reinforcement. Therefore, both thermal and mechanical properties of 3D-printed PLA/CNT nanocomposites were significantly improved when f-CNT were used, also indicating that percentages less than 1 wt% of this additive are required. Thus, the use of these nanocomposites to produce medical devices by FFF, for example, can be potentialized. Graphical Abstract: ga1 Highlights: CNT functionalization was performed for 3D-printing parts of PLA-nanocomposites. Functionalized CNT were better dispersed and assisted PLA crystallization process. Addition of only 0.5%wt of f-CNT can significantly increase the mechanical strength. Better adhesion between 3D printed layers when f-CNT was used as reinforcement. The storage modulus of 3D printed parts increased ~43% with the addition of f-CNT.